Extent and causes of unused medications among patients in rural Ethiopia: a prospective multicenter cohort study - Dawit T. Gebregeorgise; Teferi Gedif Fenta; Bart J. F. Van den Bemt; Charlotte L. Bekker (BMC, 2024)
Abstract Background Medication waste poses health, economic, and environmental challenges. However, the extent among patients living in rural areas is underexplored. This study assessed the proportion of prescribed medications remaining unused by patients living in rural areas of Ethiopia, and identify the causes thereof and disposal practices. Methods A prospective multicenter cohort study was conducted in 5 rural health centers in Ethiopia. Patients (≥ 18 years), who received a prescription for acute or chronic medication for pick up from the outpatient pharmacy were included. After 3 months, participants received a house visit by a health employee during which a questionnaire was verbally administered to assess the quantity of unused medication, reason thereof, and disposal practices used. Data were analyzed using descriptive statistics and multivariate logistic regression to identify factors associated with presence of unused medications. Results In total, 178 patients participated. Up to 136 out of 601 (22.6%) dispensed medications ended up unused, mainly antibiotics and analgesics, with an average economic value of $0.37. Of 178 patients, 72 (40.4%) ended up with unused medication, and 15 (8.4%) did not use 80% or more of the prescribed quantity. Early discontinuation of therapy was the main reason (61.8%) for patients' ending with unused medication. Patients reported to primarily dispose of unused medication either through the toilet (43.6%), household garbage (22.7%), burning (13.6%), or returning it to the pharmacy (2.7%). Medications dispensed to be administered with two or more-unit doses at a time were more likely to remain unused (adjusted OR 1.6 [1.0-3.4]) compared to medications dispensed to be administered one-unit dose. Conclusion A substantial amount of prescribed medications remains unused by patients in rural areas, frequently not properly disposed. Interventions are needed to ensure medications are not wasted and reduce the unwanted consequences.